Odor and Odorous Compound Emissions from Manure of Swine Fed Standard and Dried Distillers Grains with Soluble Supplemented Diets. Issue 3 (1st May 2016) - Trabue, Steven; Kerr, Brian; Scoggin, Kenwood
Abstract : This study was conducted to determine the impact of diets containing dried distillers grains with solubles (DDGS) on emissions of odor and odorous compounds from swine manure storage. Twenty‐four pigs were fed either a corn–soybean meal (CSBM) diet or a diet containing 35% DDGS over a 42‐d feeding trial. Their waste was collected and transferred to individual manure storage containers. Manure from pigs fed diets containing DDGS had significantly lower odorant emissions expressed in animal units for hydrogen sulfide (H2 S) and ammonia (NH3 ) ( P < 0.05) compared with pigs fed the CSBM diet, but emissions of volatile fatty acids and phenolic compounds were significantly higher ( P < 0.05) for manures from animals fed the DDGS diet. There was no significant difference for indole compound emissions due to the dietary treatment applied. Emissions of volatile organic compounds (VOCs) from manure accounted for less than 0.1% of carbon consumed for either diet. There were no significant differences in odor emissions for either diet as quantified with human panels or measured as the sum total of the odor activity value. Manure odors from pigs fed the CSBM diet were dominated by H2 S, whereas animals fed the diet containing DDGS were dominated by VOCs. Core Ideas: Odor emission is controlled by fed ingredients. Odor emission from DDGS diets was dominated by volatile organic compounds. Emission of ammonia from manure was between 30 and 50% N consumed. Emission of H2 S from manure was between 3 and 10% of S consumed. Emission of volatile organic compounds from manure was <0.1% of C consumed.